2012
DOI: 10.1080/09297049.2011.613811
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processing and executive functioning in children and adults with Tourette's syndrome

Abstract: Tourette's syndrome (TS) is predominantly a childhood disorder, with many of those who meet diagnostic criteria in childhood experiencing a remission of symptoms in adulthood. This indicates that the influence of TS on cognitive and emotional processing can best be understood by examining performance in both adults and children with TS. The present study examined emotional processing using a battery of face and prosody tasks with increasing levels of difficulty (same-different emotion discrimination, emotion n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…However, the sample of TS-only patients in this study was rather small ( n = 11), making it hard to draw conclusions on this base. Finally, letter number sequencing is not affected in children with TS [ 90 ], which can be explained by the fact that much of the variance in this test is explained by digit span [ 91 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sample of TS-only patients in this study was rather small ( n = 11), making it hard to draw conclusions on this base. Finally, letter number sequencing is not affected in children with TS [ 90 ], which can be explained by the fact that much of the variance in this test is explained by digit span [ 91 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
“…However, impairments were also found in non-comorbid patients [ 133 ]. Few studies found no impact of comorbidity on the Purdue Pegboard [ 90 ], the Grooved Pegboard [ 90 , 137 ] and the Finger tapping test [ 137 ]. While performance on the Purdue Pegboard was shown to improve following CBT [ 133 ], a recent study showed that performance on this task was unrelated to symptoms improvement following CBT in a very large sample of adults with TS [ 134 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence shows that rates of aggressive behaviors do not differ between subjects with TS and healthy controls, whereas those with comorbid TS+ADHD demonstrate similar rates of aggression as subjects with ADHD alone [56••, 62-66]. Children with TS and ADHD show subtle deficits in emotional-processing tasks, particularly of anger, relative to healthy controls and TS-affected children without ADHD [67]. A clinical study that compared problems with executive functioning in children with ADHD, ASD, and TS relative to healthy controls found increased problems with regulating emotions in children with TS [68•].…”
Section: Aggression In Ts and Adhdmentioning
confidence: 99%
“…Maladaptive cognitions or problems processing external stimuli are associated with ADHD and OCD [72,99,108]. Children with TS+ADHD show subtle impairments on tasks measuring emotional processing compared to healthy controls or to children with TS only, especially when processing anger items [67]. Aggressionprone children suffering from ODD or other disruptive behaviors also experience cognitive deficits that contribute to maladaptive functioning [16••, 109-111].…”
Section: Psychosocial Factors Of Ts and Aggressionmentioning
confidence: 99%